2018
DOI: 10.4236/aim.2018.83012
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Infection among Pregnant Women at Pumwani Maternity Hospital, Nairobi, Kenya: Bacterial Etiologic Agents, Antimicrobial Susceptibility Profiles and Associated Risk Factors

Abstract: Urinary Tract Infections (UTIs) during pregnancy are among the most common infections worldwide and can lead to poor perinatal and maternal outcomes. This study determined the prevalence of UTIs during pregnancy, associated risk factors and antimicrobial susceptibility profiles of associated bacterial pathogens. A cross-sectional study was conducted among 210 pregnant women attending antenatal clinic at Pumwani Maternity hospital. Their social-demographic profiles were obtained using a structured questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
27
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 13 publications
13
27
10
Order By: Relevance
“…The sensitivity patterns exhibited by the Gram-negative isolates in our study have been demonstrated in other studies in Ethiopia, Nigeria, Uganda, Kenya, Cameroon and South Africa [ 8 10 , 13 , 16 , 17 ]. The prevalence of MRSA was 33.3% in our study which was higher than that found by Onyango et al at Puwani Hospital in Nairobi in 2018 (20%) [ 18 ]. The presence of ESBL producers among the Enterobacteriaceae in our study was 29.0% with Klebsiella at 25% and E. coli at 32.5% respectively.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…The sensitivity patterns exhibited by the Gram-negative isolates in our study have been demonstrated in other studies in Ethiopia, Nigeria, Uganda, Kenya, Cameroon and South Africa [ 8 10 , 13 , 16 , 17 ]. The prevalence of MRSA was 33.3% in our study which was higher than that found by Onyango et al at Puwani Hospital in Nairobi in 2018 (20%) [ 18 ]. The presence of ESBL producers among the Enterobacteriaceae in our study was 29.0% with Klebsiella at 25% and E. coli at 32.5% respectively.…”
Section: Discussioncontrasting
confidence: 71%
“…The presence of ESBL producers among the Enterobacteriaceae in our study was 29.0% with Klebsiella at 25% and E. coli at 32.5% respectively. This was higher than that by Onyango et al 2018 in Kenya (19%), Musa Sekikubo et al 2017 at Mulago (18%) but was less than that found by Sabrina et al 2010 in Tanzania (32.5%) [ 10 , 18 , 19 ]. A meta-analysis by Feizollah Mansouri et al 2019 found the pooled prevalence of ESBL-producing Enterobacteriaceae of 25% with 45% in Africa, 33% in India, 5% in Europe and 3% in North America.…”
Section: Discussioncontrasting
confidence: 54%
“…Higher levels of antimicrobial resistances than reported in our study with greater than 30% towards ceftazidime, cefotaxime, ceftriaxone, ciprofloxacin, aztreonam and gentamicin in A. baumannii, E. coli, P. aeruginosa and K. pneumoniae from blood, tracheal aspirates, wound, pus and urine samples have been documented in Kenya [25] [26]. Our study however show an increase in antimicrobial resistance in environmental compartments compared to a previous study conducted in Kakamega town in Kenya [27].…”
Section: Discussioncontrasting
confidence: 48%
“…This was higher than study from Addis Ababa (74.0%), 19 and lower than reports from Bahir Dar 91.3%, 53 Jigjiga 96.0%, 54 Gondar 95.0%, 9 Dire Dawa 100.0% 18 and Kenya 96.0%. 43 This indicates that MDR was found to be very high to the commonly used antibiotics in the study area. The possible reason for this rise in MDR might be repeated, inappropriate, and incorrect use of antimicrobial agents in empirical treatment and poor infection control strategies which in turn raise the prevalence of resistant microorganism in the community.…”
Section: Discussionmentioning
confidence: 77%
“…In the present study, E. coli was the most predominant isolate with an isolation rate of 17 (33.3%) which is in line with most of the studies conducted locally such as Gondar, 9 Bahir Dar, 17 Addis Ababa 19 and Dire Dawa, 18 and also elsewhere in the world including Brazil, 6 Iran, 1 Nigeria, 26 India, 27 Nepal, 25 Cameroon, 13 Pakistan, 42 and Kenya. 43 The major contributing factor for isolating such higher rate of E. coli might be due to the significant abundance of E. coli as fecal flora which in turn via contamination ascend through genitalia to cause UTI and due to numerous virulence factors used for colonization and invasion of the urinary epithelium such as P-fimbriae or pili adherence factors which mediate the attachment of E. coli to uroepithelial cells. CoNS were the second dominant bacterial isolates in our study with an overall isolation rate of 30%, and comparable results were reported from other previous studies conducted in Gondar, 9 Bahir Dar, 17 Addis Ababa, 19 Dire Dawa, 18 Zimbabwe 44 and India.…”
Section: Discussionmentioning
confidence: 99%